The atomists, Leucippus and Democritus : fragments : a text and translation with a commentary - Leucippus (Phoenix pre-Socratics (Toronto, Ont.), 1999)
A new presentation of the evidence for the thought of Leucippus and Democritus, based on the original sources. Includes the Greek text of the fragments with facing English translation, notes, commentary, and complete indexes and concordances.